1996
DOI: 10.1074/jbc.271.9.5007
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Unsaturated 14-Carbon Fatty Acids Found on the N Termini of Photoreceptor-specific Proteins

Abstract: In the vertebrate retina, a number of proteins involved in signal transduction are known to be N-terminal acylated with the unusual 14 carbon fatty acids 14:1n-9 and 14:2n-6. We have explored possible pathways for producing these fatty acids in the frog retina by incubation in vitro with candidate precursor fatty acids bearing radiolabels, including [3H]14:0, [3H]18:1n-9, [3H]18:2n-6, and [3H]18:3n-3. Rod outer segments were prepared from the radiolabeled retinas for analysis of protein-linked fatty acids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…These metabolites are formed through peroxisomal ␤oxidation, and the main product is the 16-carbon metabolite, 16:3n-6 (1). Additional studies have shown that the retina can convert linoleic acid to the 14:2n-6 that is utilized for acylation of photoreceptor proteins (25). The present work indicates that EPA is converted to similar products, and as in the case of arachidonic acid, the most abundant metabolite that accumulates under all of the conditions tested is 16:4n-3, the omega-3 analogue of 16:3n-6.…”
Section: Discussionsupporting
confidence: 60%
“…These metabolites are formed through peroxisomal ␤oxidation, and the main product is the 16-carbon metabolite, 16:3n-6 (1). Additional studies have shown that the retina can convert linoleic acid to the 14:2n-6 that is utilized for acylation of photoreceptor proteins (25). The present work indicates that EPA is converted to similar products, and as in the case of arachidonic acid, the most abundant metabolite that accumulates under all of the conditions tested is 16:4n-3, the omega-3 analogue of 16:3n-6.…”
Section: Discussionsupporting
confidence: 60%
“…FAMEs were analyzed by gas-liquid chromatography as described (Tanito et al, 2008). Fatty acid phenacyl esters (FAPES) were prepared from total lipid extracts for high performance liquid chromatography (HPLC) analysis as previously described (DeMar and Anderson 1997; DeMar et al, 1996). …”
Section: 2 Materials and Methodsmentioning
confidence: 99%
“…Anderson and co-workers have found that frog retina outer rod segments converted radiolabelled oleic acid 18:1 (n 9) 76 to 152 and 18:2 (n 6) 114 to 153, presumably by two rounds of -oxidation, and that 18:3 (n 3) or 14:0 151 were not incorporated into either 14:1 (n 9) 152 or 14:2 (n 6) 153 (Scheme 40). 209 There does not appear to be a 5Z desaturase operative in this system.…”
Section: Chordatamentioning
confidence: 78%